TERORISME DAN AKAR FUNDAMENTALISME PESANTREN (Studi Kasus Pesantren di Riau dan Multikulturalisme Agama) - Bambang Hermanto (Lembaga penelitian dan pengabdian kepada masyrakat, 2009)
Fundamentalism is understood by most people who come from a boarding schools in Indonesia. a decent religion was transformed into an act of terrorism that is based on a shallow understanding of religious fundamentalism. fundamentalist attitude in all religions so that every religion has fundamentalism in school of teachings. If each religion can not empathize with each and tolerant, then the difference between conviction will greatly influence the future of Indonesia. For context of Riau, the Malays people who inhabit this land of yellow impudent can become the balance of geographical Riau prone to acts of terrorism. In addition to the fact that nature is revealed terrorism travel of Riau none solidarity involvement of all elements that are in it with terrorism